2007
DOI: 10.1097/ico.0b013e31806c782a
|View full text |Cite
|
Sign up to set email alerts
|

Attachment to and Penetration of Conventional and Silicone Hydrogel Contact Lenses by Fusarium solani and Ulocladium sp. In Vitro

Abstract: To our knowledge, this is the first report that F. solani produces coiled penetration pegs in the matrices of SH hydrophilic soft contact lenses similar in morphology to those found in HEMA lenses. F. solani attaches firmly to SH lenses and rarely penetrates the lens matrix, but viable fungal propagules may remain on the lens after vigorous rinsing with MPS. Failure to use a manual cleaning-disinfection procedure may help to explain the increased incidence of Fusarium keratitis associated with contact lens wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
(42 reference statements)
2
21
0
Order By: Relevance
“…In agreement with the results reported by these investigators, we also found, using both the industry standard ISO 14729 and XTT-based methods, that planktonic Fusarium and Candida cells were susceptible to lens disinfectants. The recent Fusarium keratitis outbreaks have been associated with loss of antimicrobial activity during contact lens storage, selective growth of Fusarium in globules of partially dried deposits of MoistureLoc, use of a "no-rub" procedure to care for contact lenses, a general decrease in effectiveness of MoistureLoc solution compared with other lens solutions, and binding of Fusarium to different contact lens materials (4,26). Our current findings suggest that the ability of Fusarium spp.…”
Section: Vol 52 2008 Fusarium and C Albicans Biofilms On Contact Lmentioning
confidence: 77%
See 2 more Smart Citations
“…In agreement with the results reported by these investigators, we also found, using both the industry standard ISO 14729 and XTT-based methods, that planktonic Fusarium and Candida cells were susceptible to lens disinfectants. The recent Fusarium keratitis outbreaks have been associated with loss of antimicrobial activity during contact lens storage, selective growth of Fusarium in globules of partially dried deposits of MoistureLoc, use of a "no-rub" procedure to care for contact lenses, a general decrease in effectiveness of MoistureLoc solution compared with other lens solutions, and binding of Fusarium to different contact lens materials (4,26). Our current findings suggest that the ability of Fusarium spp.…”
Section: Vol 52 2008 Fusarium and C Albicans Biofilms On Contact Lmentioning
confidence: 77%
“…Similar to our findings, attachment to the lens surface ranged from a loose association of conidia and hyphae to firmly attached hyphae that were difficult or impossible to remove (4). It is noteworthy that Ahearn et al (4) reported that the two isolates of "F. solani" tested differed in their ability to attach to hydrogel contact lenses. Given that multilocus DNA sequence typing has shown that these isolates represent two phylogenetically distinct species within the FSSC (39) (GSU AFR4 [FSSC 1-b] and GSU 81036 [FSSC 4-a]), it is possible that some of the observed differences may be species or strain specific.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is possible that co-contamination of the lens case with P. aeruginosa and F. solani may decrease the antifungal activity of ReNu with MoistureLoc. Numerous researchers have attempted to explain the epidemic; causative factors hypothesized include direct uptake of alexidine by the contact lenses (thereby reducing its antimicrobial efficacy) [44], exposure of ReNu with MoistureLoc to prolonged temperature elevation [32], reduced antimicrobial activity of evaporated ReNu with MoistureLoc [45], enhanced growth of Fusarium spp on contact lens and lens case biofilm [46], direct penetration of Fusarium spp into soft contact lenses [47], and patient non-compliance with manufacturer's recommendations (e.g.. storing the lenses without emptying and replacing the solution in the case every day, just adding extra solution to the case, etc.) [14,45].…”
Section: Discussionmentioning
confidence: 99%
“…A number of laboratories have recently reported the findings of experimental studies seeking to account for the outbreak related to use of ML (1,7,11,13,14,18,19,27,34). Imamura et al concluded that the formation of biofilms on various types of contact lenses and the consequent reduced susceptibility to lens cleaning solutions played a role in the outbreak of Fusarium keratitis (14).…”
mentioning
confidence: 99%